1999
DOI: 10.1038/sj.bjp.0702543
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐dependent isoflurane effects on depolarization‐evoked glutamate and GABA outflows from mouse brain slices

Abstract: 1 The synaptic concentrations of glutamate and g-aminobutyric acid (GABA) are modulated by their release and re-uptake. The e ects of general anaesthetics on these two processes remain unclear. This study evaluates the e ects of iso¯urane, a clinically important anaesthetic, on glutamate and GABA release and re-uptake in superfused mouse cerebrocortical slices. 2 Experiments consisted of two 1.5-min exposures to 40 mM KCl in 30 min intervals. During the second exposure, di erent concentrations of iso¯urane wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Previous studies support the conclusion that clinically relevant concentrations of volatile anesthetics do not affect K ϩ -evoked excitatory amino acid release (Minchin, 1981;Kendall and Minchin, 1982;Lingamaneni et al, 2001) or GABA release (Minchin, 1981;Kendall and Minchin, 1982;Lecharney et al, 1995;Salford et al, 1997;Lingamaneni et al, 2001). Inhibition of K ϩ -evoked release of glutamate (Miao et al, 1995;Liachenko et al, 1999) or GABA Liachenko et al, 1999) by isoflurane has been reported. Interpretation of results obtained in brain slices (Liachenko et al, 1999), however, is (Buggy et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies support the conclusion that clinically relevant concentrations of volatile anesthetics do not affect K ϩ -evoked excitatory amino acid release (Minchin, 1981;Kendall and Minchin, 1982;Lingamaneni et al, 2001) or GABA release (Minchin, 1981;Kendall and Minchin, 1982;Lecharney et al, 1995;Salford et al, 1997;Lingamaneni et al, 2001). Inhibition of K ϩ -evoked release of glutamate (Miao et al, 1995;Liachenko et al, 1999) or GABA Liachenko et al, 1999) by isoflurane has been reported. Interpretation of results obtained in brain slices (Liachenko et al, 1999), however, is (Buggy et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
“…Inhibition of K ϩ -evoked release of glutamate (Miao et al, 1995;Liachenko et al, 1999) or GABA Liachenko et al, 1999) by isoflurane has been reported. Interpretation of results obtained in brain slices (Liachenko et al, 1999), however, is (Buggy et al, 2000). Failure to compare anesthetic effects on release evoked by additional secretagogues (Lingamaneni et al, 2001) makes it difficult to interpret results obtained only with elevated KCl.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations suggested that the effects of isoflurane on the electrical properties of neurons can account for between 62 and 78% of the inhibitory effects of isoflurane on excitatory post synaptic currents (Wu et al 2004). In contrast with the studies from Hemmings, Richards, and Wu, other groups have reported more robust dose-dependent inhibition of KCl-evoked neurotransmitter release by clinically relevant concentrations of isoflurane (Larsen et al 1994;Liachenko et al 1999;Miao et al 1995). Larsen et al, for example, reported ϳ0.33, 1, and 2 MAC isoflurane inhibited KCl-evoked glutamate release from rat hippocampal slices by 31, 42, and 51%, respectively (Larsen et al 1994).…”
Section: Discussionmentioning
confidence: 69%
“…Anesthesia has been shown to alter mostly tonic glutamate levels and in some circumstances phasic glutamate release dynamics (Liachenko et al, 1998(Liachenko et al, , 1999Rutherford et al, 2007). Recordings in freely moving animals allow for monitoring glutamate neurotransmission without the effects of anesthesia.…”
Section: Studies In Freely Moving Rats and Micementioning
confidence: 99%